Public administration challenges of the sanitary and phytosanitary agreement's notification provision - Cash, John (John A.) (My University, 2015)
The WTO committee on the Trade and Development looks at developing countries’ special needs and provides assistance for agreement implementation, technical cooperation and increased participation in the global trading system. Technical assistance is provided to assist developing countries as they adjust to WTO rules and disciplines. Technical assistance often includes support to help build a country’s public-administration infrastructure so that it can better carry out WTO work, handle disputes, and implement trade standards. This paper focuses on the public-administration challenges associated with a particular provision of a particular WTO trade agreement and highlights the need for continued technical assistance for developing countries.
Sponsored by the Marjorie J. and Richard L.D. Morse Family and Community Public Policy Scholarship
Citation: Cash, J. A. (2004). Public administration challenges of the sanitary and phytosanitary agreement's notification provision. Unpublished manuscript, Kansas State University, Manhattan, KS.
Keywords: Agreement on the Application of Sanitary and Phytosanitary Measures (1995 January 1); Food adulteration and inspection--Law and legislation--Developing countries; Plant inspection--Law and legislation--Developing countries; Animal welfare--Law and legislation--Developing countries; Reports; Reports